Artefact Matters. (3rd March 2016) - Hengeveld, Bart; Frens, Joep; Deckers, Eva
Abstract: In this paper we consider the current lively discussion on how and whether to formalize the Research through Design (RtD) approach and argue that the role of the artefact is essential but underexposed in this discussion. Through three case studies we investigate the different roles the artefact can have within RtD and show that design relevant knowledge is in the process of designing the actual artefact, in the artefact itself as well as in its evaluation. Considering the role of the artefact more thoroughly portrays insights on how theory is built in the RtD approach, as well as in matters that do or do not make sense to formalize in the first place. We discuss this at the end of the paper through identifying similarities and differences between the three cases.